PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MELIPAT KERTAS ASTURO PADA ANAK KELOMPOK A TK DEWI SARTIKA PULE MODO LAMONGAN - Sutiani, - -; Sholihul Anshori, - - (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
Research on children in TK A Dewi Sartika Pule ModoLamongan motivated by the fine motor skills were lacking earlychildhood, especially in terms of ability to hold the paper, put it withthe thumb, forefinger, and middle finger, press the crease to thefingertips, folding creases according to the form so that the need foraction is through folding. This is necessary because the learning israrely done. One of the ways to stimulate development throughactivities asturo paper folding. This study uses a type of actionresearch and qualitative research approaches designed in the form ofa repeating cycle consisting of four phases: planning, action,observation and reflection. Data collection techniques in this studyusing observation data analysis techniques while using descriptivestatistical analysis based reflection cycles. The subjects of this studywere a group of TK A Dewi Sartika Pule Modo Lamongan the numberof 15 children. Based on the data obtained from the first cycle ofassembly 1 activity for teachers to get an average value of 50% in thesecond cycle 3 meeting increased to 94%, the activity children receivean average of 44% in the second cycle 3 meeting increased to 94%, andfine motor skills obtain an average value of 46% at the confluence of 3increased to 88%. Based on data from the first cycle of this research iscontinuing on the second cycle because of the success criteria of thisaction is ≥ 75%. Based on data from the second cycle of action researchis declared successful.